Governing Smart Cities: an Analysis of Governance and Sustainability of Smart City Initiatives in Cimahi City - Naufal Aji Satria (Jurnal Multidisiplin Indonesia, 2026)
This article analyzes the governance and sustainability of smart city initiatives in Cimahi City from a public policy perspective. The main issue studied is the extent to which smart city development in medium-sized cities can be sustainable and institutionalized within the local government system. The purpose of this paper is to examine the smart city initiatives in Cimahi City through the lens of smart city governance, governance policy services (GPS), policy implementation, institutionalization, and policy sustainability. The methods used include descriptive qualitative studies based on the analysis of policy documents, local government performance reports, and relevant literature reviews. The results of the study show that Cimahi City has experienced significant progress in digital governance, as reflected in the achievement of high Smart City Index and SPBE Index scores, as well as the development of integrated digital services. However, the sustainability of smart city initiatives still faces challenges in terms of collaboration across non-governmental actors, strengthening policy institutionalization, and ensuring the consistency of long-term regulatory and budgetary support. This article concludes that the sustainability of smart cities in Cimahi City is largely determined by the ability of local governments to integrate digital initiatives into collaborative, coordinated, and long-term oriented governance.